Autologous leukocyte-poor platelet-rich plasma injection in the treatment of knee osteoarthritis: short-term clinical effect analysis - YANG Lei; JING Doudou; LIU Mingxi; GUO Zhenye; YANG Binai; LIN Shuzhong; ZHANG Demei; GUO Fengyan; LIU Jin (Zhongguo shuxue zazhi)
Objective To investigate short-term clinical efficacy of autologous leukocyte-poor platelet-rich plasma(LP-PRP) treatment of knee osteoarthritis(KOA). Methods 85 cases of patients with Keligren Lawrence grade Ⅰ-Ⅲ knee osteoarthritis in Peking University First Hospital Taiyuan Hospital (Taiyuan Central Hospital) from 2022 to 2023 were collected for autologous LP-PRP collection and quality assessment using a blood component separator, and all patients were treated with autologous LP-PRP. The degree and function of knee pain were assessed by visual analog scale(VAS) and knee arthritis index scale(WOMAC) at 1, 3 and 6 months after injection. Knee MRI was performed after 6 months of treatment, and the MRI imaging changes before and after treatment were compared. Different influencing factors in the treatment results were grouped and analyzed, mainly including platelet concentration in LP-PRP and K-L grading of knee joint. According to the platelet concentration in LP-PRP, it was divided into three grades, which are low concentration[(<800)×109/L], medium concentration[(800-1 000)×109/L], and high concentration[(>1 000)×109/L]; According to the K-L grade of the knee joint, the severity of knee osteoarthritis was divided into three grades: Ⅰ、Ⅱ、Ⅲ. Results The VAS and WOMAC scores at 1, 3 and 6 months after LP-PRP treatment were significantly lower than those before treatment, and the difference was statistically significant (P<0.05). There was a statistically significant difference in the therapeutic effect of different levels of platelet concentration, and when the platelet concentration was more than 1 000×109/L, the significant effect was the most obvious(P<0.05). The therapeutic effect of different levels of platelet concentration was statistically significant(P<0.05). MRI showed that the articular cartilage signal was significantly improved after treatment. Conclusion Autologous LP-PRP injection into knee cavity for the treatment of KOA has a good short-term clinical effect in relieving knee pain.